Multi-domain destructuring in the early phases of psychosis: a multicentric phenomenological and psychometric case-control study - Ottone Baccaredda Boy; Ottone Baccaredda Boy; Giuseppe Pierpaolo Merola; Andrea Patti; Andrea Patti; Bernardo Bozza; Dario Flaccomio; Marco Faldi; Giulia Pitt; Luca Papini; Vincenzo Pecoraro; Ilaria Noschese; et al. (Frontiers in Behavioral Neuroscience)
IntroductionThe study aims to evaluate symptomatic differences through psychometric tools comparing patients in the early stages of psychotic development with those exhibiting a more established symptomatology. Our hypothesis was that the early phase in adolescent patients is accompanied by quantitatively and qualitatively distinct symptomatology compared to adults.MethodsWe assessed 116 participants–consisting of 14 to 65 years old patients with psychotic or mood symptoms–using psychometric tools and a clinical interview. The tools explored psychotic, depressive and anxiety dimensions, to provide a multifaceted assessment of the recruited individuals and help at categorizing them into diagnostic subclasses.ResultsWe compared patients with psychotic symptoms (early-onset and lifetime) to patients with mood disorders (unipolar depression or bipolar disorder without psychotic symptoms). Psychotic symptoms intensity was significantly higher in the early-onset group compared to the lifetime group and was markedly greater than in the two other groups. It was also observed that the intensity of anxiety and depressive symptoms in the psychosis group were significantly higher in the early-onset subgroup.ConclusionOur findings suggest that the clinical presentation of early-onset patients, typically striking in its symptomatology, is reflected by elevated scores on scales not routinely used for psychotic symptoms. This may be attributed to the pervasive destructuring of personality and reality characteristic of early psychotic experiences.